The importance of a project charter in digital marketing project management - Kim, O.; Kudinova, M.; Kovalova, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The study focuses on the important issue of marketing project management, in accordance with the PMBOK guidelines, which contain knowledge and best practices in project management, as well as the standard that was used as a basis for the development of the international standard ISO 21500. The relevance of the topic is determined by the fact that one of the best practices in project management is to draw up a project charter, which is the main framework document that defines the project goals, stakeholders, key milestones in the project schedule, the main value created by the project, the main risks of the project, and other attributes that are established in the list of best practices. The project charter performs the following functions: official approval of the project by the sponsor (customer), fixing the main parameters of the project, and coordinating the project with stakeholders. The purpose of the study is to compare the functions and significance of the project charter and brief for use in digital marketing. Research methods include a comparative analysis of project management artifacts for use in digital marketing. The main results of the study: it is supplemented that the essence of marketing projects is to fulfill marketing tasks and achieve marketing SMART goals according to the characteristic features of the project - a certain scale, time constraints and budgetary constraints. It has been found that marketing projects can be implemented by both functional and cross-functional teams, according to cascade, adaptive and hybrid methodologies, which are determined by the theory and best practices of project management. It is substantiated that in the course of implementing a marketing project, the main processes, such as planning, execution, and closure, as well as project management artifacts, in particular, the project charter, can be implemented. It is proved that the project charter is an important document that performs a number of functions in project management - it fixes the main project parameters approved by the sponsor (customer), the team, risks, and high-level budget. Thus, this artifact has an important function of harmonizing the relationship between project stakeholders (between the sponsor and the project manager, between the project manager and the team, between the project manager and other stakeholders, and other possible combinations of relationships) in terms of planning, implementing, and completing the project, which helps to avoid conflicts at different stages of the project life.